Reducing catheter-associated urinary tract infections: a systematic review of barriers and facilitators and strategic behavioural analysis of interventions - Atkins, Lou; Sallis, Anna; Chadborn, Tim; Shaw, Karen; Schneider, Annegret; Hopkins, Susan; Bunten, Amanda; Michie, Susan; Lorencatto, Fabiana (Implementation science : IS, 2020)
Background Reducing the need for antibiotics is crucial in addressing the global threat of antimicrobial resistance. Catheter-associated urinary tract infection (CAUTI) is one of the most frequent device-related infections that may be amenable to prevention. Interventions implemented nationally in England target behaviours related to catheter insertion, maintenance and removal, but the extent to which they target barriers to and facilitators of these behaviours is unclear. This strategic behavioural analysis applied behavioural science frameworks to (i) identify barriers to and facilitators of behaviours that lead to CAUTI (CAUTI-related behaviours) in primary, community and secondary care and nursing homes; (ii) describe the content of nationally adopted interventions; and (iii) assess the extent to which intervention content is theoretically congruent with barriers and facilitators. Methods A mixed-methods, three-phased study: (1) systematic review of 25 studies to identify (i) behaviours relevant to CAUTI and (ii) barriers to and facilitators of CAUTI-related behaviours, classified using the COM-B model and Theoretical Domains Framework (TDF); (2) content analysis of nationally adopted CAUTI interventions in England identified through stakeholder consultation, classified using the Behaviour Change Wheel (BCW) and Behaviour Change Techniques Taxonomy (BCTTv1); and (3) findings from 1 and 2 were linked using matrices linking COM-B and TDF to BCW/BCTTv1 in order to signpost to intervention design and refinement. Results The most frequently reported barriers to and facilitators of CAUTI-related behaviours related to ‘environmental context and resources’; ‘knowledge’; ‘beliefs about consequences’; ‘social influences’; ‘memory, attention and decision processes’; and ‘social professional role and identity.’ Eleven interventions aiming to reduce CAUTI were identifed. Interventions were primarily guidelines and included on average 2.3 intervention functions (1–5) and six BCTs (2–11), most frequently ‘education’, ‘training’ and ‘enablement.’ The most frequently used BCT was ‘information about health consequences’ which was used in almost all interventions. Social professional role and identity and environmental context and resources were targeted least frequently with potentially relevant BCTs. Conclusions Interventions incorporated half the potentially relevant content to target identifed barriers to and facilitators of CAUTI-related behaviours. There were missed opportunities for intervention as most focus on shaping knowledge rather than addressing motivational, social and environmental influences. This study suggests that targeting motivational, social and environmental influences may lead to more effective intervention design and refinement.